2007
DOI: 10.1007/s10551-007-9360-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Ethical Attitudes in Mainland China and Hong Kong

Abstract: China, ethical attitudes, gender, Hong Kong, moral judgment, religion,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 49 publications
4
66
0
Order By: Relevance
“…As has been seen in previous studies (e.g. Lam and Shi, 2008), higher education did not seem to raise ethical standards. In fact, the estimated coefficients of the education dummies were never negative, and were in some cases positive, indicating that individuals with more education were more willing to express an acceptance of questionable practices.…”
Section: Noel Y M Siu and Kit-chun Joanna Lamsupporting
confidence: 79%
See 2 more Smart Citations
“…As has been seen in previous studies (e.g. Lam and Shi, 2008), higher education did not seem to raise ethical standards. In fact, the estimated coefficients of the education dummies were never negative, and were in some cases positive, indicating that individuals with more education were more willing to express an acceptance of questionable practices.…”
Section: Noel Y M Siu and Kit-chun Joanna Lamsupporting
confidence: 79%
“…Market competition also limited the workers' security of employment and their risks in the event of sickness and old age. In another China study, Lam and Shi (2008) examine the ethical perceptions of working people and concluded that competitive pressure has not been conducive to ethical behavior. In contrast with these findings, Dubinsky and Ingram failed to find such relationship in their study (1984).…”
Section: For-profit Vis-à-vis Non-profit Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study by Lam and Shi (2008) in China found that the ethical attitudes of the employees are not impacted by them being employed by foreign-investment firms. The proposed explanation for this phenomenon is that, the ethical standards imposed by the multinational companies operating in countries that are less developed may not be similar with the standards imposed in their headquarters located in the developed countries.…”
Section: Ownership Structure Foreign Ownershipmentioning
confidence: 97%
“…While Daoism takes a passive approach to ethical questions, it and the Chinese Community Traditions are not insignificant in shaping ethical behavior in China. Lam and Shi (2007) found that religion played an important role in determining ethical orientation in Chinese culture. While Christianity correlated more closely with higher educational standards, followers of the traditional Chinese religious tradition showed a greater concern for ethical behavior than individuals with no religious orientation.…”
Section: Laozi and Zhuangzimentioning
confidence: 99%